Transplant tourism and invasive fungal infection. (April 2018) - Al Salmi, I.; Metry, A.M.; Al Ismaili, F.; Hola, A.; Al Riyami, M.; Khamis, F.; Al-Abri, S.
Abstract: Background: Deceased and live-related renal transplants (RTXs) are approved procedures that are performed widely throughout the world. In certain regions, commercial RTX has become popular, driven by financial greed. Methods: This retrospective, descriptive study was performed at the Royal Hospital from 2013 to 2015. Data were collected from the national kidney transplant registry of Oman. All transplant cases retrieved were divided into two groups: live-related RTX performed in Oman and commercial-unrelated RTX performed abroad. These groups were then divided again into those with and without evidence of fungal infection, either in the wound or renal graft. Results: A total of 198 RTX patients were identified, of whom 162 (81.8%) had undergone a commercial RTX that was done abroad. Invasive fungal infections (IFIs) were diagnosed in 8% of patients who had undergone a commercial RTX; of these patients, 76.9% underwent a nephrectomy and 23.1% continued with a functioning graft. None of the patients with RTXs performed at the Royal Hospital contracted an IFI. The most common fungal isolates were Aspergillus species (including Aspergillus flavus, Aspergillus fumigatus, Aspergillus nidulans, and Aspergillus nigricans ), followed by Zygomycetes. However, there was no evidence of fungal infection including Aspergillus outside the graft site. Computed tomography (CT) findings showed infarction of the graft, renal artery thrombosis, aneurysmal dilatation of the external iliac artery, fungal ball, or just the presence of a perigraft collection. Of the total patients with IFIs, 23.1% died due to septic shock and 53.8% were alive and on hemodialysis. The remaining 23.1% who did not undergo nephrectomy demonstrated acceptable graft function. Conclusions: This is the largest single-center study on commercial RTX reporting the highest number of patients with IFI acquired over a relatively short period of time. Aspergillus spp were the main culprit fungi, with no Candida spp being isolated. A high index of suspicion might be the most reasonable means to reduce the possible very poor outcomes. Improving legal transplant programs and strengthening the associated laws could prevent commercial transplant tourism.